Estudo dos fatores que afetam a lealdade dos consumidores brasileiros de ferramentas on-line de reserva hoteleira - Krüger, Gabriel Nogueira (2018)
The objective of this study is to evaluate the factors affecting the loyalty of Brazilian online hotel reservation users. A total of 227 suitable answers for the study were collected from a previous contact database, in all the 5 macro-regions of Brazil. Subsequently, the structural equation modeling (SEM - PLS) was used to analyze the data found. The results show that the tested model presented a good statistical adequacy, besides evidencing the propensity of the Brazilians to prioritize satisfaction in the decision to reuse an online booking platform, and navigation functionality was presented as the main catalyst for this feeling. These results show the need for the hotel industry to develop virtual platforms that foster the satisfaction of its users and to develop a loyal relationship. The originality of this study focuses on the use of SEMPLS to understand how to catalyze loyalty among Brazilian online booking tools users.